Cancer in beluga whales from the St Lawrence Estuary, Quebec, Canada: A potential biomarker of environmental contaminatio - Martineau, Daniel; Lair, Stephanie; De Guise, Sylvain; P. Liscomb , Thomas; Beland, Pierre (J. Cetacean Res. Manage., 1999)
A population of approximately 500 white whales (Delphinapterus leui us) inhabits a short stretch of the St Lawrence Estuary which drains one of the most industrialised areas of the world. Over a 12-year period (1983-1994), 73 carcasses out of 175 beluga2 whales reported stranded on the St Lawrence Estuary shoreline have been examined. Of these 73 carcasses, 14(1 9<>;) were affected by 15 different malignant tumours (cancers), one animal being affected by two different types of cancer. Overall, 23 r/i of necropsied sexually mature animals were affected by cancer. Forty percent of the 35 cancer cases reported world-wide in cetaceans occurred in this population. The estimated annual incidence rate (AIR) of cancer in St Lawrence beluga whales, a minimum figure of 233/100,000 animals, is much higher than that reported for any other population of cetaceans, and is similar to that of man, and of hospitalised cats and cattle. More specifically, the AIR of small intestinal cancers in the studied population, a minimum figure of 83/100,000 animals, is much higher than that observed in man and all animals, except in sheep in certain parts of the world, where an environmental carcinogen is believed to be etiologically involved.